Two original articles in the field of sleep medicine published in 1932 and 1934 by the authors from the Faculty of Medicine in Belgrade (on the occasion of the 90th anniversary of neuropsychiatric service in Serbia) - Janković, Slavko M; Sokić, Dragoslav V.; Vojvodić, Nikola M.; Ristić, Aleksandar J.; Kovačević, Maša; Kostić, Vladimir S. (Vojnosanitetski pregled, 2017)
xxx